PEACE EDUCATION BASED ON LOCAL WISDOM NOSARARA NOSABATUTU - Ratu, B; Misnah, Misnah; Amirullah, M. (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
This article aims to discuss the development of a culture of peace through a local wisdom-based peace education program Nosarara Nosabatutu. Nosarara Nosabatu is a Kaili ethnic local wisdom, in the city of Palu, Central Sulawesi, with the main concept being peacein society through a spirit of brotherhood, togetherness, unity and unity, family, and peace. Nosarara Nosabatu needs to be implemented in educational programs for young people, especially for students in schools, in order to build a culture of peace in the people of Palu. This article uses the library research method. The research findings are: 1) the values of peace in the local wisdom of Nosarara Nosabatutu; and 2) the prospect of developing guidance and counseling based on local wisdom Nosarara Nosabatutu to develop a culture of peace in the School.